ANALISA ORGANIZATIONAL CITIZENSHIP BEHAVIOR YANG DIPENGARUHI OLEH BUDAYA ORGANISASI DENGAN KEPUASAN KARIER & KOMITMEN ORGANISASI SEBAGAI VARIABEL MEDIASI (Studi Empirik Pada Kantor Pelayanan Perbendaharaan Negara di Jawa Tengah) - Jumiarsih .; Endah Winarti HS; SB Handayani (LPPM STIE DHARMAPUTRA SEMARANG, 2021)
AbstractThe purpose of this study was to analyze the influence of organizational culture on organizational citizenship behavior with career satisfaction and organizational commitment as mediating variables. The population in this study were employees of the State Treasury Service Office in Central Java as many as 452 people. Sampling in this study using the Purposive Judgment Sampling method, a total of 102 people who can be processed. The results of hypothesis testing show that organizational culture has a significant positive effect on career satisfaction, organizational culture has a significant positive effect on organizational commitment. Career satisfaction has a significant positive effect on organizational citizenship behavior, organizational commitment has a significant positive effect on organizational citizenship behavior, organizational culture has a significant positive effect on organizational citizenship behavior. Furthermore, the results of the Sobel test, career satisfaction mediating organizational culture on organizational citizenship behavior concluded that career satisfaction can mediate the influence of organizational culture on organizational citizenship behavior. The results of the Sobel test, organizational commitment mediating the influence of organizational culture on organizational citizenship behavior concluded that organizational commitment can mediate the influence of organizational culture on organizational citizenship behavior. Keywords: Organizational culture, career satisfaction, organizational commitment, organizational citizenship behavior AbstrakTujuan penelitian ini adalah untuk menganalisis pengaruh budaya organisasi terhahap organizational citizenship behavior dengan kepuasan karier dan komitmen organisasi sebagai variabel mediasi. Populasi dalam penelitian ini adalah pegawai Kantor Pelayanan Perbendaharaan Negara di Jawa Tengah sebanyak 452 orang. Pengambilan sampel pada penelitian ini menggunakan metode Purposive Judgment Sampling, sejumlah 102 orang yang bisa diproses. Hasil pengujian hipotesis menunjukan budaya organisasi berpengaruh positif signifikan terhadap kepuasan karier. Budaya organisasi berpengaruh positif signifikan terhadap komitmen organisasi. Kepuasan karier berpengaruh positif signifikan terhadap organizational citizenship behavior. Komitmen organisasi berpengaruh positif signifikan terhadap organizational citizenship behavior. Budaya organisasi berpengaruh positif signifikan terhadap organizational citizenship behavior. Selanjutnya hasil uji Sobel, kepuasan karier dalam memediasi budaya organisasi terhadap organizational citizenship behavior menyimpulkan kepuasan karier dapat memediasi pengaruh budaya organisasi terhadap organizational citizenship behavior. komitmen organisasi dalam memediasi pengaruh budaya organisasi terhadap organizational citizenship behavior menyimpulkan komitmen organisasi dapat memediasi pengaruh budaya organisasi terhadap organizational citizenship behavior. Kata kunci: Budaya organisasi, kepuasan karier, komitmen organisasi, organizational citizenship behavior